2019
DOI: 10.1002/jso.25502
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical trial of proton therapy for chordoma and chondrosarcoma: Feasibility assessment

Abstract: Background/Objectives Proton therapy (PRT) has emerged as a treatment option for chordomas/chondrosarcomas to escalate radiation dose more safely. We report results of a phase I/II trial of PRT in patients with chordoma/chondrosarcoma. Methods Twenty adult patients with pathologically confirmed, nonmetastatic chordoma or chondrosarcoma were enrolled in a single‐institution prospective trial of PRT from 2010 to 2014. Seventeen patients received adjuvant PRT and three received definitive PRT. Median dose was 73.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
(42 reference statements)
2
14
0
Order By: Relevance
“…Radiotherapy, especially proton therapy, has been reported to improve local control and PFS of chordoma. 2 In our study, the multivariate Cox regression analysis showed that radiotherapy has no relation with PFS. This indicates that chordoma is resistant to radiotherapy, and more studies are needed to explore its role in prolonging PFS.…”
Section: Discussionmentioning
confidence: 47%
“…Radiotherapy, especially proton therapy, has been reported to improve local control and PFS of chordoma. 2 In our study, the multivariate Cox regression analysis showed that radiotherapy has no relation with PFS. This indicates that chordoma is resistant to radiotherapy, and more studies are needed to explore its role in prolonging PFS.…”
Section: Discussionmentioning
confidence: 47%
“…The effect of proton radiotherapy in an adjuvant setting has been unclear, whereas recent studies have reported favourable early results with proton radiotherapy as definitive treatment, with local control rates of over 90% at 3 years [15,19]. As an adjuvant treatment, proton radiotherapy was reported to result in a local control rate of 33-95% with a relatively short follow-up (Table 5) [15,19,34,35,38]. The wide range of local control rates among these studies might be attributed to the heterogeneous settings among the study cohorts, such as margin status and pre-/postoperative use of proton radiotherapy, which hinder effective comparisons of the outcomes associated with the adjuvant use of conventional photon radiotherapy [40].…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistencies might be attributed to the unstandardized treatment paradigms among multiple institutions, such as timing of treatment (pre-or post-operative), type of radiotherapy (photon, proton, or carbon ion), and radiation dose. Notably, the benefits of proton radiotherapy in an adjuvant setting have been unclear [34][35][36], while carbon ion [15,18,37] or proton radiotherapy [12,15,18,38] plays a role in unresectable cases.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hypoxia is a cause of treatment failure, and new radiotherapeutic strategies aim at delivering a stronger dose to hypoxic tumor zones to eliminate chordoma tumors [13,42]. In the same intent of improving chordoma patient response to radiotherapy, proton irradiations are used in chordomas in recent clinical trials and show better results than X-rays [43,44]. Even though proton therapy is still poorly accessible, it could be interesting to study the response of our spheroids to this kind of treatment.…”
Section: Discussionmentioning
confidence: 99%